2002
DOI: 10.1152/japplphysiol.01221.2001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tower climbing exercise on bone mass, strength, and turnover in orchidectomized growing rats

Abstract: To determine the effects of a tower climbing exercise on mass, strength, and local turnover of bone, 70 9-wk-old Sprague-Dawley rats were assigned to seven groups: a baseline control and three groups of sham-operated sedentary, orchidectomized (ORX)-sedentary and ORX-exercise rats. Rats voluntarily climbed a 200-cm tower to drink water from a bottle set at the top. At 4 wk, the periosteal bone formation rate (BFR), moment of inertia, bone mineral content, bone mineral density, and bending load at the midfemur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 33 publications
1
17
0
1
Order By: Relevance
“…Indeed, daughters of female patients with hip fractures have an enlarged femoral neck, suggesting that bone fragility-in humans similar to this senile osteoporosis model-may already become apparent during growth [28,29]. In line with earlier studies in rats, early hypogonadism causes a sustained cancelllous bone deficit as well as an increase in bone resorption markers in both SAMP6 and SAMR1 [17]. Yet, earlier reports in SAMP6 mice could not demonstrate an upregulation of osteoclast formation and activity after orch [12,13].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Indeed, daughters of female patients with hip fractures have an enlarged femoral neck, suggesting that bone fragility-in humans similar to this senile osteoporosis model-may already become apparent during growth [28,29]. In line with earlier studies in rats, early hypogonadism causes a sustained cancelllous bone deficit as well as an increase in bone resorption markers in both SAMP6 and SAMR1 [17]. Yet, earlier reports in SAMP6 mice could not demonstrate an upregulation of osteoclast formation and activity after orch [12,13].…”
Section: Discussionsupporting
confidence: 78%
“…Androgens are essential for the development of a male skeletal phenotype during growth. Similar to humans, hypogonadism in rodents, as induced by orchidectomy at puberty, results in low bone mass acquisition as well as low bone strength [15][16][17]. Orchidectomy in male rodents reduces periosteal bone formation and increases bone turnover, hereby impairing, respectively, cortical and trabecular bone mass acquisition [18].…”
Section: Introductionmentioning
confidence: 99%
“…A substantial increase in bone resorption occurred, but only a small decrease in muscle mass and no increase in fat mass. In male Sprague-Dawley rats, ORX causes a significant reduction in strength (Brown et al, 2001), with no change in muscle mass (Wolden-Hanson et al, 1989;Notomi et al, 2002;Iwamoto et al, 2003). Similarly, ORX does not decrease muscle mass in Wistar rats (Antonio et Life Sciences 79 (2006) 411 -415 www.elsevier.com/locate/lifescie al., 1999Ferry et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Voluntary tower climbing is a light resistance exercise that creates little stress and strain and has been used in several studies. 5,9,[14][15][16][17] We previously demonstrated that voluntary tower climbing exercise increased bone mass and strength mainly by increasing bone formation in growing, 10) orchidectomized, 15) or ovariectomized osteopenic rats.…”
mentioning
confidence: 99%
“…7) Animal exercise models are used to examine the preventive or recovery eŠect of exercise on bone mass and strength as endpoints of an experiment. Animal studies using voluntary wheel running, 11) jumping, 12) treadmill running, 13) or voluntary climbing 9,14,15) have demonstrated the beneˆcial eŠect of increased load on bone mass and mechanical properties. Voluntary tower climbing is a light resistance exercise that creates little stress and strain and has been used in several studies.…”
mentioning
confidence: 99%